Peculiarities of in-Stent Thrombosis and Restenosis in Coronary Arteries Post-COVID-19: A Systematic Review of Clinical Cases and Case Series - Pivina L; Batenova G; Omarov N; Ygiyeva D; Messova A; Alibayeva G; Jamedinova U; Kurumbayev R; Pivin M (Open Access Emergency Medicine)
Lyudmila Pivina,1 Gulnara Batenova,1 Nazarbek Omarov,1 Diana Ygiyeva,1 Assylzhan Messova,1 Galiya Alibayeva,2 Ulzhan Jamedinova,1 Ruslan Kurumbayev,1 Maksim Pivin3 1Department of Emergency Medicine, Semey Medical University, Semey, Abay Region, Kazakhstan; 2Semey Emergency Hospital, Semey, Abay Region, Kazakhstan; 3Nuclear Medicine Department, Center of Nuclear Medicine and Oncology, Semey, Abay Region, KazakhstanCorrespondence: Lyudmila Pivina, Email semskluda@rambler.ruBackground: One of the most serious complications of coronary artery stenting is restenosis and in-stent thrombosis; their prevalence can reach 20– 25%. Stent thrombosis can be acute (up to 24 hours), subacute (24 hours to 30 days), late (30 days to 1 year), and very late (> 1 year after previous stenting). In the patients with COVID-19 in intensive care units, the proportion of those with elevated troponin levels reached 25%.Objective: Evaluation of the association between COVID-19 and the development of in-stent thrombosis and restenosis of the coronary arteries based on the analysis of clinical cases and case series.Materials and Methods: We searched the PubMed and Scopus databases for relevant case reports and case series of stent restenosis and in-stent thrombosis associated with coronavirus infection (CVI) published between 2020 and the present. Thirty-eight full-text publications were screened and manually checked for analysis. We found 10 publications describing cases of thrombosis and restenosis of stents associated with coronavirus infection, of which only 2 were case series. In total, we analyzed 22 cases.Results: In the structure of in-stent restenosis and thrombosis, 59.1% were very late, 9.1% were late; 18.2% were considered subacute events, and 13.6% were acute events. All cases were angiographically confirmed. The main location of restenosis or thrombosis was the left coronary artery (LAD) (51.1%), thrombosis of the right coronary artery (RCA) occurred in 27.3%, and location in circumflex artery was in 22.7%. All patients had COVID-19 confirmed by a PCR test or the presence of immunoglobulins G and M. In fourteen patients (54.5%), an X-ray examination showed the presence of bilateral polysegmental infiltration.Conclusion: Analysis of publications demonstrates the association between restenosis and in-stent thrombosis in patients with coronary arteries disease (CAD) and coronavirus infection.Keywords: restenosis, in-stent thrombosis, stenting, COVID-19, coronary artery disease, case report, case series